Sebaran Spasial Terumbu Karang Di Suwarnadwipa Kecamatan Bungus Teluk Kabung Kota Padang - Astia Nur Hidayah (Jurnal Azimut, 2020)
Coral reef mapping aims to see the distribution of coral reefs from 2000, 2010 and 2020. In addition, coral reef mapping also aims to see changes in the extent and damage of coral reefs from 2000, 2010 and 2020. The method used to detect the distribution of coral reefs is lyzenga logarithmic method, while to detect damage to coral reefs the method used is the unsupervised classification method. The lyzenga logarithm method uses attenuation coefficients based on the sharpening of the pixel spectral value to a certain depth to increase the value of the reflection of coral reef objects and the unsupervised classification method uses the sensitivity of the spectral values ​​of each pixel to coral reef objects. The results of the interpretation there was a significant change in the area of ​​coral reefs from 2000 to 2010 and 2010 to 2020. The interpretation of images from 2000 to 2010 detected a decrease in the area of ​​1.19 hectares. In 2010 to 2020 it detected a decrease in area of ​​28.87 hectares. The classification results detected an increase in the area of ​​damaged coral reefs from 2010 to 2020 as much as 8.74 hectares. The two methods used have differences in the level of accuracy, the lyzenga logarithmic method has an accuracy rate of 88.89% while the unsupervised classification method shows an accuracy of 86.12% so the lyzenga logarithmic method is the most suitable method for detecting coral reefs in Suwarnadwipa, Bungus Teluk District. Kabung City of Padang.